The Blindness of an Invisible Man: An Exploration of Ellison’s Female Characters - Madison Elkins (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2014)
Questions have long been raised about the female characters in Invisible Man who often appear to be objectified or stereotyped. Especially in light of Ellison’s professed opinions against the dangers of stereotyping as minority oppression, the depiction of his female characters seems to be fundamentally hypocritical. It is the dominant critical opinion among feminist scholars that Ellison’s treatment of female characters is not only hopelessly misogynistic, but, more importantly, undermines the telos of the novel and enervates its social claims. While it is a valid exercise to analyze Ellison’s female characters in this way, this opinion fails in two critical ways to assess the novel on its own terms. The invisible man’s misogynistic attitude is not a male-centric novel’s myopic flaw, but ultimately a device, a mechanism employed by Ellison to develop the protagonist and to brilliantly, if painfully, crystallize the theme of societal invisibility.